2014
DOI: 10.1007/s10792-013-9876-6
|View full text |Cite
|
Sign up to set email alerts
|

The expression of vascular endothelial growth factor in pterygium tissue of atopic patients

Abstract: The exact pathogenesis of pterygium has not been completely elucidated. Growth factors have been considered to play a role in pterygium formation. Vascular endothelial growth factor (VEGF) is one of the principal mediators of angiogenesis, fibroblast stimulation and tissue remodeling in allergic conditions. The aim of this study was to compare the association between pterygium and VEGF gene expression between atopic and non-atopic individuals. At first visit, all patients with pterygium underwent blood tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…RNA was reverse transcribed using the Prime Script™ RT reagent kit (Perfect Real Time; TaKaRa, Tokyo, Japan) according to the manufacturer’s instructions. cDNA was then amplified by RT-PCR using the primers TfR: 5ʹ-TCTGACACGTCTGCCTACCCATTCG-3ʹ (forward) and 5ʹ-TATGATGGTTCACTCACGGAGCTTCG-3ʹ (reverse) [ 22 ]; VEGF: 5ʹ-ATGACGAGGGCCTGGAGTGTG-3ʹ (forward) and 5ʹ-CCTATGTGCTGGCCTTGGTGAG-3ʹ (reverse) [ 23 ]; and GAPDH: 5ʹ-AGAAGGCTGGGGCTCATTTG-3ʹ (forward) and 5ʹ-AGGGGCCATCCACAGTCTTC-3ʹ (reverse). Primers were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was reverse transcribed using the Prime Script™ RT reagent kit (Perfect Real Time; TaKaRa, Tokyo, Japan) according to the manufacturer’s instructions. cDNA was then amplified by RT-PCR using the primers TfR: 5ʹ-TCTGACACGTCTGCCTACCCATTCG-3ʹ (forward) and 5ʹ-TATGATGGTTCACTCACGGAGCTTCG-3ʹ (reverse) [ 22 ]; VEGF: 5ʹ-ATGACGAGGGCCTGGAGTGTG-3ʹ (forward) and 5ʹ-CCTATGTGCTGGCCTTGGTGAG-3ʹ (reverse) [ 23 ]; and GAPDH: 5ʹ-AGAAGGCTGGGGCTCATTTG-3ʹ (forward) and 5ʹ-AGGGGCCATCCACAGTCTTC-3ʹ (reverse). Primers were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Although pterygium is a benign disease, it is also considered to be a neoplastic-like disorder with its uncontrolled proliferation, migration, angiogenesis, and recurrence [1]. It has been identified that the expression of genes associated with cell proliferation and angiogenesis, such as PCNA, mutant p53, MAP kinase signaling pathway, matrix metalloproteinases, and VEGFA, is higher in the pterygium than normal conjunctiva tissues [26]. Such properties make pterygium similar to a tumor in some ways.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios sugieren que IL-13 es la citocina Th2 predominante en la superficie ocular normal, razón por la cual encontramos una expresión basal en los tejidos que puede modificarse al aumentar el grado de extensión de Pt 14 . Por otro lado, se ha descrito en biopsias de Pt obtenidas de pacientes atópicos y no atópicos un aumento significativo en la expresión de IL-4 y una disminución evidente de IFN-γ, lo que concuerda con los resultados observados en nuestras muestras 15 . Es importante enfatizar que, a pesar de que la expresión de IFN-γ se encuentra muy disminuida en todos los grados de extensión del Pt, podemos observar que, en las biopsias correspondientes a los grados I, III y IV, la expresión del factor transcripcional Th1 (T-bet) se encuentra aumentada, lo que sugiere que en el microambiente del Pt existe el estímulo principal de la diferenciación Th1 (IL-12), pero no en la cantidad suficiente para inducir la polarización 3,16 .…”
Section: Discussionunclassified